2021
DOI: 10.3171/2019.10.jns192414
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram to predict the progression-free survival of clival chordoma

Abstract: OBJECTIVEChordoma shows poor patient prognosis because of its high recurrence rate. Even though many clinical factors and biomarkers are reported to be associated with prognosis, no prediction model has been applied clinically. Thus, the authors aim to derive and validate a prognostic nomogram to predict progression-free survival (PFS) of chordoma.METHODSA total of 201 patients were randomly divided into a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 22 publications
2
23
0
Order By: Relevance
“…We found no signi cant difference, which is consistent with several studies [32,2]. Several previous studies showed that dural penetration [37,7] and age [29,5] were associated with long-term outcomes, and we demonstrated that they were not independent risk factors after multivariate analysis [23,36].…”
Section: Other Risk Factors For Outcomesupporting
confidence: 92%
See 2 more Smart Citations
“…We found no signi cant difference, which is consistent with several studies [32,2]. Several previous studies showed that dural penetration [37,7] and age [29,5] were associated with long-term outcomes, and we demonstrated that they were not independent risk factors after multivariate analysis [23,36].…”
Section: Other Risk Factors For Outcomesupporting
confidence: 92%
“…To the best of our knowledge, this is the largest series of SBCs surgically treated by single surgical team, and we found that surgery should be the initial treatment for primary SBCs. GTR is the surgical goal and should be applied in both primary and recurrent SBCs [36]. History of surgery, larger tumor volume, and tumor location (lower clivus, extension from the midline to the paramedian region) are independent risk factors for GTR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of this sequence has resulted in up to a threefold improvement in contrast-to-noise ratio when compared to T1 and T2/fluid-attenuated inversion recovery (FLAIR) MRI sequences [ 60 ]. Hybrid quantitative susceptibility mapping has also been used as a method to visualize the GPi and, similar to FGATIR MRI, it has shown reproducibility across centers [ 61 ]. When utilizing imaging for direct targeting, attention should be directed not only to a target point, but also to the position of the DBS electrode array relative to the optimal target volume.…”
Section: Targeting and Intraoperative Physiology Of The Gpi: Pearls And Pitfallsmentioning
confidence: 99%
“…Our DBS team has implanted over 850 GPi DBS leads over the past 18 years, and many of the previously mentioned aspects of this section of the commentary pertain to observations and insights based on our cumulative experience [ 59 , 61 , 63 ]. Within the sensorimotor territory, positioning the DBS electrode 3 mm lateral to the medial internal capsule–GPi border, and 3–5 mm anterior to the posterior internal capsule–GPi border seems to be, in our experience, the optimal site for chronic therapeutic stimulation when using omnidirectional ring electrodes.…”
Section: Targeting and Intraoperative Physiology Of The Gpi: Pearls And Pitfallsmentioning
confidence: 99%